2022
DOI: 10.5194/amt-15-1007-2022
|View full text |Cite
|
Sign up to set email alerts
|

Cloud condensation nuclei (CCN) activity analysis of low-hygroscopicity aerosols using the aerodynamic aerosol classifier (AAC)

Abstract: Abstract. The aerodynamic aerosol classifier (AAC) is a novel instrument that size-selects aerosol particles based on their mechanical mobility. So far, the application of an AAC for cloud condensation nuclei (CCN) activity analysis of aerosols has yet to be explored. Traditionally, a differential mobility analyzer (DMA) is used for aerosol classification in a CCN experimental setup. A DMA classifies particles based on their electrical mobility. Substituting the DMA with an AAC can eliminate multiple-charging … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…The CCN activity of aerosols, namely the fraction of particles activated into cloud droplets, can be directly measured by the continuous‐flow streamwise thermal‐gradient CCN counter (CCNC). The most commonly used CCNC was developed and commercialized by Droplet Measurement Technologies (DMT) (Lance et al., 2006; Roberts & Nenes, 2005), which has been widely applied in both field observation and laboratory experiment of aerosol CCN activity (Gohil & Asa‐Awuku, 2022; Kerminen et al., 2012; Kuang, Xu, et al., 2020; Paramonov et al., 2015; Tomi Raatikainen et al., 2013). This instrument consists of a continuous flow tube in which the walls are kept saturated with water and a positive wall temperature gradient is maintained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCN activity of aerosols, namely the fraction of particles activated into cloud droplets, can be directly measured by the continuous‐flow streamwise thermal‐gradient CCN counter (CCNC). The most commonly used CCNC was developed and commercialized by Droplet Measurement Technologies (DMT) (Lance et al., 2006; Roberts & Nenes, 2005), which has been widely applied in both field observation and laboratory experiment of aerosol CCN activity (Gohil & Asa‐Awuku, 2022; Kerminen et al., 2012; Kuang, Xu, et al., 2020; Paramonov et al., 2015; Tomi Raatikainen et al., 2013). This instrument consists of a continuous flow tube in which the walls are kept saturated with water and a positive wall temperature gradient is maintained.…”
Section: Introductionmentioning
confidence: 99%
“…Using the default cut off, however, can lead to 30% overestimation of the bulk CCN number concentration measurements for SS lower than 0.1% as unactivated particles might be counted (Yang et al., 2012). In addition, size‐resolved CCN activity measurements were widely performed for accurate CCN number predictions and model validation, and the data were also used to derive aerosol hygroscopicity parameter κ under supersaturated conditions (Deng et al., 2011; Gohil & Asa‐Awuku, 2022; Liu et al., 2018; Moore et al., 2010; Petters & Kreidenweis, 2007). There might be large deviations in retrieved aerosol hygroscopicity if the size‐resolved CCN activation curve was biased because of the misidentified CCN within specific diameter ranges.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional Köhler (TK) theory, the droplet is assumed to be dilute, and the water activity follows Raoult's law; such that the water 35 activity equals the water mole fraction, and the dilute droplet water activity coefficient is assumed to be unity. For water-soluble particles like inorganic ammonium sulfate (Rose et al, 2008) and sucrose (Dawson et al, 2020;Gohil and Asa-Awuku, 2022), TK can accurately predict their water uptake behavior. However, TK does not work so well for atmospherically relevant and abundant particles that are partially water soluble or water insoluble (Kumar et al, 2009;Tang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The droplet formation of water-insoluble particles has been previously described with adsorption activation models (Hatch et al, 2012;Kumar et al, 2009;Lintis et al, 2021;Malek et al, 2022;Navea et al, 2017;Pajunoja et al, 2015;Tang et al, 2016). Brunauer, Emmett, and Teller (BET) adsorption isotherm models are typically applied for multilayer adsorption analysis of water uptake on clays (Hatch et al, 2012) 45 and fly ash (Navea et al, 2017). Lintis et al, 2021 applied the Dubinin-Serpinsky model for soot and concluded that nucleation occurred at oxidized and hydrophilic surface sites on the soot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation